Digital Assets in the Inheritance Vortex: Testing the Readiness of Conventional Law and the Concept of Joint Property in Modern Families - Siti Murni (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2025)
Conventional inheritance and marriage laws govern joint property. The legal status of these assets is unclear; whether they are inherited or joint property is difficult to determine. This type of research uses a normative legal research approach realized through the Library Research method. The data analysis technique that will be applied is qualitative content analysis, conducted interactively and continuously throughout the research process. The results of the study indicate that: 1). The Classification and Legal Status of Digital Assets in Inheritance and Joint Property is that digital assets can be classified into two main categories: assets with direct financial value (such as cryptocurrencies and e-wallets) and assets with indirect economic value (such as commercial social media accounts and NFTs). 2). Technical and Legal Challenges in Identifying, Proving, and Transferring Digital Assets are: First, identification challenges due to the virtual and hidden nature of digital assets often make heirs unaware of their existence. Second, problems proving ownership due to limited access to private keys, passwords, and platform policies that prohibit the transfer of ownership. Third, problems with the transfer of rights due to the absence of a clear legal mechanism for transferring ownership of digital assets to heirs, which has the potential to result in the assets being permanently lost. 3). Legal reconstruction and future solutions to fill regulatory gaps include: First, amending the Civil Code and the Marriage Law to explicitly recognize digital assets. Second, establishing specific regulations governing digital asset inheritance procedures and requiring digital platforms to provide inheritance protocols. Third, strengthening the role of notaries and educating the public about the importance of recording digital assets in wills, as well as developing a voluntary digital asset registration system.